URBANISM OF EXCEPTION:: Camps and inhabitation - Boano, Camillo (Revista Jatobá, 2021)
This paper can be considered an attempt to think on what a camp does rather than on what it is. Camps seem to arrest, fix in time and space lives, stripping political agency away from bodies and render bare lives; materialise principle of exclusions, control and spatial precepts of modernism through its heavily loaded political semantics. Camps explicitly determines the other, the unknown and the uncontrolled, the monstrous and the needed. Following what Mezzadra and Neilson, called “the different assemblages of power and the different forces of capital” that shape territories and spaces to answer the question I wish to use somehow playfully the concept of ‘dispossession’ developed by Butler and Athanasiou and the one of inhabitation by Agamben to reflect on the camp as a site, inextricably intertwined with the promise of death, police and disappearance regularly and invariably fulfilled and the incomplete, unfinished possibility of inhabiting. The paper try to suggest that camps are sites where one asks what it means to inhabit in the abyssal ambivalence of resisting death––exhausting and holding onto life.